1999
DOI: 10.1093/carcin/20.9.1747
|View full text |Cite
|
Sign up to set email alerts
|

Induction of melanoma in TPras transgenic mice

Abstract: In order to study the oncogenesis of melanocytes, transgenic mouse lines were established that express a mutated human Ha-ras (TPras) gene in pigment producing cells. The ras transgenic mice exhibit an altered phenotype, including melanocytic hyperplasia and a muted agouti coat, indicative of hyperproliferative melanocytes. These mice and their wild-type littermates have been subjected to a variety of carcinogenesis protocols, including 7, 12-dimethylbenz-[a]anthracene (DMBA), 12-O-tetradecanoylphorbol-13-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…Ras activation has been shown to contribute to melanoma tumor development (55)(56)(57). Our earlier results showed that Ras is required for MGSA/GRO␣-induced melanocyte transformation (36).…”
Section: Discussionmentioning
confidence: 83%
“…Ras activation has been shown to contribute to melanoma tumor development (55)(56)(57). Our earlier results showed that Ras is required for MGSA/GRO␣-induced melanocyte transformation (36).…”
Section: Discussionmentioning
confidence: 83%
“…Transgenic mice that express a mutant form of H-ras specifically in melanocytes showed melanocytic hyperplasia with intense skin pigmentation (9), which after treatment with carcinogens progressed into skin melanoma with metastasis formation in lymph nodes and lung (10). Breeding of Tyr::H-Ras V12G transgenic mice on an INK4a/ARF-or p53-deficient background resulted in the development of highly vascularized but amelanotic melanomas resembling nodular melanoma (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…While marginally active, Apomine was found to be well tolerated and was not myelosuppressive, which would make it a possible candidate for combination therapy with myelosuppressive agents. The stabilization of disease seen in the Phase I clinical trial and the low toxicity associated with Apomine, led to the investigation of this agent in a TPras transgenic mouse melanoma prevention model [10,11]. The TPras mice express a mutated Ha-ras gene in pigment producing cells, which leads to development of cutaneous melanoma following topical treatment with dimethylbenzanthracene (DMBA).…”
Section: Introductionmentioning
confidence: 99%